Dysfunctional Epstein-Barr virus (EBV)-specific CD8(+) T lymphocytes and increased EBV load in HIV-1 infected individuals progressing to AIDS-related non-Hodgkin lymphoma. - van Baarle, D; Hovenkamp, E; Callan, M; Wolthers, K; Kostense, S; Tan, L; Niesters, H; Osterhaus, A; Mcmichael, A; van Oers, M; Miedema, F (2001)
Acquired immunodeficiency syndrome-related non-Hodgkin lymphomas (AIDS-NHL) are thought to arise because of loss of Epstein-Barr Virus (EBV)-specific cellular immunity. Here, an investigation was done to determine whether cellular immunity to EBV is lost because of physical loss or dysfunction of EBV-specific cytotoxic T cells. Data on EBV-specific cellular immunity were correlated with EBV load. For comparison, individuals who progressed to AIDS with opportunistic infections (AIDS-OI) and long-term asymptomatics (LTAs) were studied. The number of virus-specific T cells was detected using tetrameric HLA-EBV-peptide complexes; function of these EBV-specific T cells was determined using the interferon-gamma (IFN-gamma) Elispot assay. It was observed that EBV-specific CD8(+) T cells were present in normal numbers in human immunodeficiency virus (HIV)-infected individuals. However, their functional capacity was decreased compared with HIV(-) individuals. In AIDS-NHL patients, EBV-specific T cells were not physically lost in the course of HIV-1 infection but showed progressive loss of their capability to produce IFN-gamma in response to EBV peptides. This loss of function correlated with lower CD4(+) T-cell numbers and was accompanied by increasing EBV load. In HIV-1-infected LTA individuals, in whom CD4(+) T-cell numbers were maintained, and progressors to AIDS-OI, IFN-gamma-producing EBV-specific T cells were stable and EBV load remained stable or decreased in the course of HIV infection, suggestive of immune control. Our data indicate that functional loss of EBV-specific CD8(+) T cells with a concomitant increase in EBV load may play a role in the pathogenesis of AIDS-NHL.